The Influence of Health Education Using Media Booklets About the Importance of Hemoglobin Levels to Increase Knowledge of Pregnant Women in the Work Area of the Ngemplak Public Health Center - Indah Ambarwati; Sulastri Sulastri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hemoglobin is a component of red blood cells or erythrocytes which functions to bind oxygen and deliver it to all the body's tissue cells. One of the health problems that develop in pregnant women is low hemoglobin (Hb) levels. Anemia is the main cause of morbidity and death in pregnant women. Anemia during pregnancy is defined as a hemoglobin level lower than 10 g/dl. Knowledge of pregnant women about anemia is one of the factors that play a role in the incidence of iron deficiency anemia in pregnant women. The purpose of this study was to determine the effect of health education using booklet media about the importance of hemoglobin levels to increase knowledge in pregnant women on knowledge before and after being given health education. This type of research is a quantitative study with a pre-experimental design through one group pre-post test design. The population of this study were all pregnant women in the first, second, and third trimesters. The research sample is 60 samples with purposive sampling technique. Data collection used a knowledge questionnaire about the importance of hemoglobin levels which had been tested for validity with a result of 0.444 and reliability with a result of 0.890 by researchers. The results of the research were carried out by the Kolmogrov-Smirnov normality test first, then the Wilcoxon Signed Rank Test was carried out. Based on the research results, it was obtained the results of hypothesis testing with a significance value of p-value 0.000 <0.05 so it can be concluded that there is an effect of health education using booklet media about the importance of hemoglobin levels to increase knowledge in pregnant women.Keywords: Hemoglobin Level, Anemia in Pregnancy, Health education, Knowledge, Booklet